Campylobacter spp. as a Foodborne Pathogen: A Review - Silva, Joana; Leite, Daniela; Fernandes, Mariana; Mena, Cristina; Gibbs, Paul A.; Teixeira, Paula (Frontiers in Microbiology, 2011)
Campylobacter is well recognized as the leading cause of bacterial foodborne diarrheal disease worldwide, causing mild to severe symptoms including serious infections of the extremities and permanent neurological symptoms. The organism is a cytochrome oxidase positive, microaerophilic, curved Gram-negative rod exhibiting corkscrew motility and is carried in the intestine of many wild and domestic animals, particularly avian species including poultry, where the intestine is colonized resulting in healthy animals as carriers. This review aims to elucidate and discuss the i) genus Campylobacter, growth and survival characteristics; ii) detection, isolation and confirmation of Campylobacter; iii) campylobacteriosis and presence of virulence factors and iv) colonization of poultry and control strategies.